تنفيذ التوجهات الاستراتيجية في القطاع العام السعودي في ضوء رؤية 2030: مراجعة للأدبيات - فرحان العنزي (مجلة ابن خلدون للدراسات والأبحاث, 2026)
هدف البحث إلى إجراء مراجعة منهجية للأدبيات التي تناولت تنفيذ الاستراتيجيات في القطاع العام السعودي في ضوء رؤية المملكة العربية السعودية 2030 بوصفها توجهًا استراتيجيًا عامًا، وذلك بهدف تحديد أبرز آليات التنفيذ الاستراتيجي، والممكنات، والمعوقات، والفجوات البحثية. واعتمد البحث منهج المراجعة المنهجية للأدبيات وفق بروتوكول PRISMA 2020، حيث جرى البحث في عدد من قواعد البيانات العلمية، وهي: PubMed، وScopus، وWeb of Science، وCINAHL، وEconLit، باستخدام أربع صيغ منطقية للبحث. ومن أصل 1171 دراسة فريدة، تم اعتماد 24 دراسة استوفت معايير التضمين المحددة بعد عملية تدقيق وفحص منهجية. وأظهرت النتائج وجود ست آليات تنفيذ مشتركة في منظمات القطاع العام السعودي، تمثلت في: برامج تحقيق الرؤية، وإدارة التغيير، وإعادة تصميم الخدمات، والتحول الرقمي، والشراكات مع القطاع الخاص، وأنظمة المراقبة وتقييم الأداء. كما أبرزت النتائج مجموعة من الممكنات الداعمة للتنفيذ، شملت: القيادة التحويلية، والتوافق الاستراتيجي مع الرؤية، والحوكمة الرشيدة، وتنمية الموارد البشرية، والبنية التحتية الرقمية. وفي المقابل، كشفت النتائج عن مجموعة من العوامل التي قد تعيق التنفيذ الاستراتيجي الفعال، من أبرزها: البيروقراطية المركزية، وفجوة المهارات، والعوائق الرقمية، وعدم الاتساق الإقليمي في التنفيذ. وخلص البحث إلى أهمية تعزيز وحدات التنفيذ المشتركة بين القطاعات، والاستثمار المنهجي في تنمية الموارد البشرية، والإدارة التدريجية للتحول الرقمي، وبناء وتفعيل أنظمة رقابة وتقييم أداء موجهة نحو الأهداف المشتركة. كما أكد أهمية الانتقال من الدراسات القطاعية إلى الدراسات المقارنة، ومن الدراسات المقطعية إلى الدراسات الطولية؛ بما يسهم في تتبع فاعلية التنفيذ الاستراتيجي عبر الزمن. This study aimed to conduct a systematic review of the literature on strategy implementation in the Saudi public sector within the framework of Saudi Vision 2030 as an overarching strategic direction, with the objective of identifying the key strategy implementation mechanisms, enabling factors, barriers, and research gaps. The study employed a systematic literature review following the PRISMA 2020 protocol. Relevant studies were retrieved from several academic databases, including PubMed, Scopus, Web of Science, CINAHL, and EconLit, using four Boolean search strategies. Out of 1,171 unique records identified, 24 studies met the predefined inclusion criteria and were included after a rigorous screening and eligibility assessment. The findings revealed six common strategy implementation mechanisms across Saudi public sector organizations: Vision Realization Programs, change management, service redesign, digital transformation, public–private partnerships, and performance monitoring and evaluation systems. The review also identified several key enablers of successful implementation, including transformational leadership, strategic alignment with Saudi Vision 2030, good governance, human resource development, and digital infrastructure. Conversely, the findings highlighted several barriers to effective strategy implementation, including centralized bureaucracy, skills gaps, digital challenges, and regional inconsistencies in implementation. The study concludes that strengthening cross-sector implementation units, systematically investing in human resource development, adopting a phased approach to digital transformation, and establishing goal-oriented performance monitoring and evaluation systems are essential for improving strategy implementation. It also emphasizes the need to shift from sector-specific studies to comparative research and from cross-sectional to longitudinal studies in order to better understand the effectiveness of strategy implementation over time.